2003
DOI: 10.1088/0957-4484/14/8/310
|View full text |Cite
|
Sign up to set email alerts
|

Selective dielectrophoretic manipulation of surface-immobilized DNA molecules

Abstract: The fabrication of nanoscale molecular devices is becoming increasingly important and research into their fabrication has intensified over the last few years. In particular, the attachment of molecular objects onto various surfaces has attracted considerable attention. Here, we report a multistep surface immobilization procedure, which allows the specific and controlled attachment of very long DNA molecules onto gold electrodes. Further, we report the effect of dielectrophoresis on these surface-bound DNA mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 26 publications
0
37
0
Order By: Relevance
“…Before immobilization of the DNA fragments onto the gold electrodes as described in detail in Ref. 24, each solution was diluted to 50 ng/ l DNA in TE (10 mM tris-HCl, 1 mM EDTA, pH 8) 1 M NaCl solution, and the YOYO-1 fluorescent intercalator (Molecular Probes, Eugene, OR, USA) was added at an intercalator to basepair ratio of 1:8. Control experiments to confirm that the DNA is tethered to the electrodes via one end only have been carried out.…”
Section: B Dna Fragment Preparationmentioning
confidence: 99%
See 3 more Smart Citations
“…Before immobilization of the DNA fragments onto the gold electrodes as described in detail in Ref. 24, each solution was diluted to 50 ng/ l DNA in TE (10 mM tris-HCl, 1 mM EDTA, pH 8) 1 M NaCl solution, and the YOYO-1 fluorescent intercalator (Molecular Probes, Eugene, OR, USA) was added at an intercalator to basepair ratio of 1:8. Control experiments to confirm that the DNA is tethered to the electrodes via one end only have been carried out.…”
Section: B Dna Fragment Preparationmentioning
confidence: 99%
“…The detection method used to confirm the presence of the DNA targets the biotin attached to the free end. 25 All of the control experiments, either using no oligonucleotides at all, complementary but nonthiolated, or noncomplementary oligonucleotides in the multistep procedure, 24 demonstrated that no -DNA was bound to the surface in the absence of suitable anchor molecules confirming that the DNA is tethered only via one end. Further, tethered -DNA was digested with BglII which cleaves the DNA close to the biotinylated end.…”
Section: B Dna Fragment Preparationmentioning
confidence: 99%
See 2 more Smart Citations
“…In the channel, the dielectrophoretic force is mainly in competition with the drag force, F drag , and thus, dielectrophoretic trapping is generally performed at low flow rate. 7 Most of the devices dedicated to DEP trapping are realized by integrating coplanar microfabricated electrodes, with geometries consisting generally of interdigitated 8 or castellated 9 electrode arrays. However, F DEP decreases quickly as the distance from the electrode surface increases.…”
mentioning
confidence: 99%